Financial Liquidity Management in Polish Enterprises In The Conditions of Non-Stable Macro-Environment - Andrzej KOZA (Communications of International Proceedings, 2024)
Financial management in modern enterprises becomes particularly important in crisis conditions. Many years of experience of scientists and researchers indicate that attention to the proper relations between the capital structure and the asset structure is the key to the success of an enterprise and a condition for its survival in the conditions of an unstable macro-environment. The COVID-19 pandemic and the war in Ukraine have left a mark on the global economy. The effects of these events also affected the Polish economy and Polish entrepreneurs. This study attempts to identify macroeconomic factors influencing the capital structure of enterprises. Particular attention was focused on the relationship between the debt structure and the structure of assets responsible for maintaining financial liquidity. Researchers have often proven that deterioration of financial liquidity is the main reason for the bankruptcy of enterprises, despite their profitability.
Keywords: macro-environment of the enterprises; capital structure management; liquidity management